Niveles de Malondialdehido y Catalasa en tejidos de cobayos nativos de la altura - Torres M., César A. (2004)
In the present study, levels of malondialdehyde (MDA), end product of lipid peroxydation, and activity of catalase, a protective enzyme, in heart , kidney, liver and lung of guinea pigs born and bred in the altilude (Cullhuay, 3642 m), and another from sea level (La Molina, 238 m), were determined, in order to establish whether there exist any differences, and better understand of the oxydative stress in high altitude natives. Tissue levels of MDA were assessed by the n-methy-l-phenylindol method, and catalase enzyme activity was evaluated using the PURPALD colorimetric method. In tissue of heart, kidney, liver and lung of high altitude guinea pig were found MDA concentrations in mmoles/g protein: 0.309, 0.158, 0.133 and 0.257, values signifieantly higher in high altitude guinea pig than in those from sea level: 0.263, 0.115, 0.097 Y 0.201 (p < 0.05); and the value of catalase activity, expressed in mmoles of formaldehyde produced/g protein: 0.693, 0.268, 0.552 and 0.311, significantly lower in those from sea level:.784, 0.319, 0.628 and 0.377 (p < 0.05). These findings make evident an association between chronic hypoxia and  increased generation of free radicals, and also that in chronic hypoxia diminishes the protective action of the antioxydative defense system, here represented by ea catalase enzyme. No significant correlations between catalase and MDA were found.